Sonographic Features of Primary Breast Lymphoma: An Analysis of 10 Cases - Liu, Xinying; Liu, Jingyun; Chen, Shuangxi (Current Medical Imaging, 2023)
Background: Primary breast lymphoma (PBL) is a rare malignant breast tumor. The literature concerning PBL ultrasound is based primarily on case reports, with only a few cases reported to date. Purpose: This study aimed to elucidate the sonographic characteristics of PBL and explore the value of ultrasonography in the preoperative diagnosis of PBL using the Breast Imaging Reporting and Data System (BI-RADS). Methods: A retrospective review of files involving a diagnosis of PBL (2013–2020) was conducted in the Department of Pathology, Zhejiang Provincial People’s Hospital, Hangzhou, and the First Affiliated Hospital of Wenzhou Medical University, Wenzhou. The clinical characteristics and sonographic features of 12 lesions in 10 patients were analyzed and discussed in light of the literature. Results: All patients, aged 50.40 ± 14.31 years (range 30–66 years), had clinically palpable lumps. Most cases were on the right breast and were unilateral. Only one patient had mucosa-associated lymphoma. The histological type of the other patients was diffuse large B-cell lymphoma (DLBCL). Ultrasonography revealed nodular and diffuse PBL lesions without internal calcification. The nodular PBL was hypoechoic or mixed hypo- to hyperechoic, with a differential lobulated shape and horizontal growth. Although color Doppler flow imaging (CDFI) showed no significant features, the ultrasound findings were categorized as BI-RADS 4 in 10 of the 12 lesions and BI-RADS 5 in two lesions. All patients were suspected of having malignancies (BI-RADS 4 or 5). Conclusion: PBL was mostly found in middle-aged and elderly women, and the right breast was more prone to the development of malignancies. PBL lesions were classified as either nodular or diffuse based on the boundaries of the tumors in the ultrasound images. Typical PBL was characterized by hypoechoic or heterogeneous lesions with circumscribed or microlobulated margins and horizontal growth. The sonographic features of the PBL lesions and the BI-RADS categorizations of the lesions analyzed suggested malignancy.
Keywords: Primary breast lymphoma